Techno-economic assessment of solar PV/fuel cell hybrid power system for telecom base stations in Ghana. Issue 1 (1st January 2021) - Odoi-Yorke, Flavio; Woenagnon, Atchou
Abstract: As the world drives towards a resilient zero-carbon future, it is prudent for countries to harness their locally available renewable energy resources. This study has investigated the possibility of deploying a solar PV/Fuel cell hybrid system to power a remote telecom base station in Ghana. The study aims to lower the levelized cost of electricity (LCOE) and reduce greenhouse gas emissions produced from the hybrid power system. Hybrid Optimization Model for Electric Renewable (HOMER) software was used to conduct the viability analysis. The results show that the LCOE produced by the PV/fuel cell hybrid system is about 0.222 USD/kWh. This LCOE outshines the current average grid tariff (0.25 USD/kWh) paid by grid-connected telecom base stations. Moreover, the LCOE is 67% cheaper than the diesel power system at the site. Likewise, the LCOE is 30% cheaper compared to a PV/battery/diesel hybrid system. Furthermore, a switch to a PV/Fuel system saves nearly 43 tCO2/yr and 67 tCO2/yr than PV/battery/diesel and diesel power systems, respectively. Sensitivity analysis shows that the system LCOE is resilient to variations in the discount rate and capital subsidies. Based on these findings, off-grid telecom sites with insufficient wind and biomass resources could opt for a PV/fuel cell system since it has been shown to be more cost-effective than diesel generating power systems under locally available market data. The study findings are vital to stakeholders, decision-makers, policymakers, and investors in Ghana and worldwide to promote low carbon technologies.